The Relationship Between Personal Hygiene and Economic Level on The Incidence of Scabies in Nur El Haq Modern Islamic Boarding School Students - Yusuf, Andini; Hadi, Santriani; Murfat, Zulfitriani; Syamsu, Rachmat Faisal; Makmun, Armanto (Jurnal Biologi Tropis, 2024)
The study, entitled " The relationship between personal hygiene and economic level on the incidence of scabies in Nur El Haq modern Islamic boarding school students". was conducted from November 2023 to January 2024. This study aims to determine the relationship of personal hygiene and economic level to the incident of scabies. This research analytical observational method with a cross sectional approach then analyzed through the Chi-Square test using the SPSS application. Based on the results of research with statistical tests obtained regarding personal hygiene and the incidence of scabies, p value of 0.029 < 0.05 was obtained, and there is no significant relationship between economic level and the incidence of scabies as shown by the p-value 0.176 <0.05. Students at the Nur El Haq modern Islamic boarding school with poor personal hygiene are more susceptible to scabies. Further research is needed regarding other variables related to scabies incidents among students at boarding school. The results of this research can be used as a reference for educating students about the importance of personal hygiene for health.